Novel fluorescent probes for sequential detection of Cu2+ and citrate anion and application in living cell imaging. (February 2019) - Chang, Yongxin; Fu, Jiaxin; Yao, Kun; Li, Bai; Xu, Kuoxi; Pang, Xiaobin
Abstract: Three novel fluorescent probes (L1, L2 and L3) derived from 2-hydroxyphenyl-4-chloromethyloxazole 8-ydroxyquinaldine were designed and synthesized. The probes showed highly selectively and sensitivity towards Cu 2+ ion through "turn off" response in DMF/H2 O solution (v/v = 1/1, 0.01 M, Tris-HCl buffer, pH 7.30). The detection limits of probes were up to 8.24 × 10 −8  M for Cu 2+ ion, which were much lower than drinking water permission concentrations by the United States Environmental Protection Agency. Sequentially, the L1-Cu 2+, L2-Cu 2+ and L3-Cu 2+ complexes detected citrate anion (CA) through "turn on" response. The probes, were also found to be reversible and recyclable toward Cu 2+ ion and CA controlled "On–Off–On" fluorescent switch and acted as molecular logic gates. Furthermore, the in vivo sensitivity experiments of Cu 2+ ion and CA were demonstrated through fluorescence imaging in living cells. Graphical abstract: In this study, we reported three novel probes L1, L2 and L3 for highly selectively and sensitivity detected Cu 2+ ion through "turn off" response in DMF/H2 O solution (v/v = 1/1, 0.01 M, Tris-HCl buffer, pH 7.30). Sequentially, the L1-Cu 2+, L2-Cu 2+ and L3-Cu 2+ complexes detected citrate anion through "turn on" response, which could be applying as molecular logic gate. Furthermore, the in vivo sensitivity experiments of Cu 2+ ion and citrate anion were demonstrated through fluorescence imaging in living cells. Highlights: Three novel fluorescent probes L1, L2 and L3 exhibited excellent selectivity and sensitivity for the sequential detection of Cu 2+ ion and citrate anions (CA). The binding modes of probes L1, L2 and L3 with Cu 2+ ion had been well demonstrated by UV–vis, fluorescence, IR and DFT calculation. The detection limit of probe L3 for Cu 2+ ion was 8.24 × 10 −8  M which lower than the U.S. EPA limits and WHO of Cu 2+ ion detection in drinking water. The probes could act as INHIBIT logic gates and applied for Cu 2+ ion and CA fluorescence imaging in living cells.